EFFECTIVE APPROACHES OF TEACHING WRITING - Tlektesov, F.M.; Yusupova, D.M. (SCIENCE and SOCIETY, 2023)
In the process of teaching writing instructors need to be able to choose appropriate approaches in order to organize lessons more productive, therefore, the role of selecting approaches is crucial in terms of explaining writing styles clearly